Prevalence, socio-economic, and associated risk factors of oral cavity parasites in children with intellectual disability from Lorestan province, Iran - Selahbarzin, Behnoush; Mahmoudvand, Hossein; Khalaf, Amal Khudair; Kooshki, Fahimeh; Farhadi, Fatemeh; Baharvand, Parastoo (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Children with intellectual disability (ID) often face challenges in maintaining proper oral hygiene due to their motor, sensory, and intellectual impairments, which can lead to compromised oral health; therefore, there is a need to enhance the oral health status of these populations and establish an effective system for administering preventive interventions. Here, we aimed to evaluate the prevalence of Entamoeba gingivalis and Trichomonas tenax among children with ID in Lorestan province, in Western Iran through parasitological and molecular methods. Methods The current descriptive investigation involved 215 in children with ID and 215 healthy children (non-ID) who were referred to health facilities in Lorestan province, Iran between October 2022 and March 2024. The prevalence of protozoa in the oral cavity was found through the utilization of both microscopic analysis and conventional polymerase chain reaction (PCR) techniques. Results The total prevalence of the E. gingivalis and T. tenax in children with ID was found to be 87 (40.5%) and 92 (42.8%) through microscopic and PCR methods, respectively. Among the positive samples, 57 (61.9%) and 35 (38.1%) children tested positive for E. gingivalis and T. tenax, respectively. In contrast, among the 215 non-ID children in the control group, 39 (18.1%) and 42 (19.5%) tested positive by microscopic and PCR methods, respectively. Among positive samples in non-ID children, 23 (54.7%) and 19 (45.3%) children were positive for E. gingivalis and T. tenax, respectively. Multiple logistic regression analysis indicated that residing in urban areas, parental education, monthly family income, and tooth brushing p<0.001) were identified as independent risk factors for oral cavity parasites. Conclusion This study identified a notable prevalence of oral cavity parasites in children with ID in Lorestan province, Western Iran. It is imperative to recognize the primary risk factors associated with these parasites, particularly inadequate teeth brushing, in order to enhance public and oral health strategies for children with ID. Therefore, pediatric dental professionals should remain vigilant regarding these risk factors to effectively recognize and address oral health issues in this population, thereby mitigating the occurrence of oral diseases and infections.